Method Validation for Pesticide Residues on Rice Grain in Aceh Besar District, Indonesia Using Gas Chromatography-Electron Capture Detector (GC-ECD) - Winarsih, Agus; Idroes, Rinaldi; Zulfiani, Utari; Yusuf, Muhammad; Mahmudi, Mahmudi; Saiful, Saiful; Rahman, Sunarti Abd (Leuser Journal of Environmental Studies, 2023)
Analysis of pesticide residues in rice in Aceh Besar District using the Gas Chromatography – Electron Capture Detector (GC-ECD) method has been carried out. This study aims to validate the analytical method and determine the pesticide residue levels of Dichlorvos, Dimethoate, Bifenthrin, and λ-Cyhalothrin in rice samples. Rice samples in branded rice were taken from the Districts of Want Jaya, Indrapuri, Darussalam, Suka Makmur, Simpang Tiga, Kuta Baro, and ground using a grinder. The powder sample was extracted by the QuEChERS method and analyzed by GC-ECD. The results of the linearity test have met the requirements with the coefficient of determination (R2), which is an average of 0.98. The LOD values ranged from 0.013 to 0.017 mg/kg, while the LOQ ranged from 0.022 to 0.079 mg/kg. The results of precision and reproducibility (% RSD, n = 6) show the values of 0.56 - 1.26% and 1.14 - 2.19%, respectively, and the accuracy value (%Recovery) shows the results of 99.71 - 101.84%, with an RSD value of 2.42 - 3.59%, meet the requirement of 20%. The results of the analysis of the sample showed that sample A had a large %Recovery value in the Dichlorvos analyte, namely 139.10%, with the calculation that the Dichlorvos analyte contained 0.0206 mg/Kg. This value has not passed the MLR set by the European Food Safety Authority, which is 0.2 mg/Kg. In the other rice samples, no pesticide residue analytes were detected. The calculation of %Recovery of each analyte in the spiked sample ranged from 80-101%, which indicated that the pesticide residue analysis carried out had good accuracy, namely the requirement of 70-120%.